2019
DOI: 10.3171/2018.6.spine171390
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fixation strength among constructs of atlantoaxial fixation

Abstract: OBJECTIVETo avoid jeopardizing an aberrant vertebral artery, there are three common options in placing a C2 screw, including pedicle, pars, and translaminar screws. Although biomechanical studies have demonstrated similar strength among these C2 screws in vitro, there are limited clinical data to address their differences in vivo. When different screws were placed in each side, few reports have compared the outcomes. The present study aimed to evaluate these multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Paramore reported a high riding C2 transverse foramen in 18% of patients [ 75 ]. A high riding vertebral artery was present in 50 to 70% of patients with Down syndrome, rheumatoid arthritis, basilar invagination, Klippel-Feil syndrome, and congenital skeletal anomalies [ 11 ]. Madawi found that the pedicle anatomy precluded safe screw placement in 20% of patients [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramore reported a high riding C2 transverse foramen in 18% of patients [ 75 ]. A high riding vertebral artery was present in 50 to 70% of patients with Down syndrome, rheumatoid arthritis, basilar invagination, Klippel-Feil syndrome, and congenital skeletal anomalies [ 11 ]. Madawi found that the pedicle anatomy precluded safe screw placement in 20% of patients [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors strongly endorse careful study of thin-slice axial and sagittal computerized tomography scans of the C1-C2 complex, to select screw length and trajectory [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases achieved satisfied reduction with symptoms relieved using this technique. 24,25 Furthermore, to increase bony fusion, 1 or 2 cross-linkages were used to the axial stability, and finally 95.8% fusion rates were observed in our study. 26 Based on our clinical experience, there are several operative nuances of using such reduction technique.…”
Section: Discussionmentioning
confidence: 56%
“…Elliott et al 22 reported that pseudarthrosis occurred in a greater proportion of patients treated with C2 pars screws (4.4%) compared with C2 pedicle screws (0.22%). In a series presented by Chang et al, 23 translaminar screws significantly lowered the success rate of C1-2 fixation (57.1% in cases of bilateral translaminar screws, and 78.9% in cases of unilateral translaminar screws) compared with bilateral C2 pedicle screws (100%). Therefore, C2 pars screws and laminar screws may not be ideal alternative options for patients with atlantoaxial instability requiring extra-rigid immobilization to maintain reduction and achieve fusion.…”
Section: Discussionmentioning
confidence: 90%